FENOMENA PERNIKAHAN USIA DINI DI DESA SUHADA KECAMATAN ENOK KABUPATEN INDRAGIRI HILIR - Yusmanita "; Yusmar Yusuf (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
The phenomenon of early marriage is a case that is more prevalent in rural than in urban areas. This study aims to determine what factors cause of premature marriages, to find out how the society view against of early marriage in the village Suhada. This study focused on the age of marriage with the educational background, knowledge, the economic system of family and religious background. Early marriage is referred to in the study is a marriage that occurs in women under 18 years. This research is descriptive qualitative, selection of informants in this study was done by using purposive sampling, the retrieval of data from informants based on certain criteria by conducting in-depth interviews to six women who married under the age of eighteen years, two parents of informants, and three community leaders in the village Suhada. The research found that the factors causing teenagers to early marriage in the village Suhada mostly from the low economic family, and low parental education and children so easily marry or approve children to get married at an early age without thinking about the negative impact that would occur if perform early marriage, so easily parents arranged child marriages though it was still early age. Parents greatly influence the formation of adolescent self-concept were married at an early age, because the child is viewed from one family were doing early marriage, there are even some informants who said that his brother also did early marriage. Community social environment and family environment has a great influence on the formation of an adolescent's self-concept. Society's view that in the neighborhood have a lot to do early marriage, so familiar when I hear the word married at an early age this happens because of the low economic factors, family, and education. The community's views are different there are pros and there are cons it depends by each individual.Keyword : Early Marriage, View Society